EFFECT OF WATER MELON SEEDS EXTRACTS (Citrullus vulgaris) ON SPERMS IN DIABETIC RAT. - Arash Khaki; Elaheh Ouladsahebmadarek; AfshinZahedi .; Behnam Ahmadnezhad (Indonesian Journal of Pharmacy, 2013)
Citrullus vulgaris is an antioxidant and has been shown to reduce oxidative stress. Previous studies confirmed that antioxidants have essential effect on infertility through participating in reactive oxygen’s species. Chronic hyperglycemia is known to cause infertility in diabetes disease. Wistar male rats (n=40) were allocated into three groups: control group(n=10), Citrullus vulgaris seeds extract (CVE) group that received 55mg/kg by gavage method (n=10), and Diabetic group that received 55mg/kg (IP) streptozotocin (STZ) (n=20). The last group was subdivided into two groups of 10. STZ group and treatment group. Treatment group received 55mg/kg (IP) STZ plus 55mg/kg CVE, daily for 4weeks; however, the control group just received an equal volume of (0.9% NaCl) daily (gavage). Diabetes was induced by a single (IP) injection of streptozotocin (55mg/kg). Animals were kept in standard condition. In 28th day, 5cc bloodn sample was taken from every rat for biochemical analysis. Collecting epididymis tissues, they were prepared for sperm analysis by WHO method. In comparison to other groups, sperm parameters were significantly increased in groups that received 55mg/kg (CVE) (P